Penerapan Masyarakat Cerdas menggunakan Obat sebagai Strategi Pencegahan Penyakit di Desa Maro Sebo - Medi Andriani; Rizky Nurhikmah; Putri Ningrum Nurin Latifah; Juwani Legistria; Annisa Putri; Eka Septi Efriami Nasution; Diana Pungky; Anitawati Sripana Br. Pasaribu; Fabiola Darma Ramadhani; Nurul Istifani (Jurnal Abdimas Kesehatan (JAK), 2026)
The implementation of the Smart Community in Using Medicines program is a strategy to improve public awareness regarding rational drug use as well as disease prevention. This community service activity was conducted in Maro Sebo Village, Jambi Luar Kota District, Muaro Jambi Regency for 30 days targeting residents of RT 01, RT 02, and students of SDN 112/IX. The methods used included socialization, counseling, and health examinations. Activities included Smart Pharmacist (Apoteker Cilik) education, nail hygiene counseling, self-medication education for cough and cold, dengue fever prevention with the introduction of natural mosquito repellent spray, and free blood pressure screening accompanied by hypertension education at the elderly integrated health post. Initial observations showed that the dominant health problems included hypertension, diabetes mellitus, respiratory tract infections, cough and cold, and digestive disorders in children. The results indicated high community participation in improving personal hygiene awareness, rational drug use, and disease prevention. Blood pressure screening revealed that most elderly participants had stage 1 hypertension. This program demonstrates that the implementation of a smart community in using medicines can be an effective strategy to improve healthy lifestyle behavior among the community.